Teachers and Multicultural Education: How do Moderate Islamic Teachers Perceive Freedom of Expression and Hate Speech? - Husni, Husni; Rizal, Soni Samsu; Munandar, Didih Syakir; Selamet, Selamet (Dinamika Ilmu, 2024)
Due to the high number of incidents involving the suppression of religious freedom, West Java Province is frequently regarded as the most intolerant province in Indonesia. Islamic religious teachers are among the actors who perpetuate bigotry and commit breaches. This research aims to explore the views of moderate Islamic Religious Education teachers regarding freedom of expression and hate speech on social media, as well as the significance of multicultural education. This descriptive research method is based on data obtained from moderate Islamic religious education teachers in West Java. Data were gathered via in-person interviews, telephone conversations, email, and social media platforms. Moderate Islamic religious teachers in West Java assert that limitations on individuals' freedom of speech may be implemented in order to protect the human rights of others or groups and are enforced following explicit and measurable legal norms. They argue that equitable legal enforcement can effectively address the pervasive dissemination of hate speech on social media. Nevertheless, multicultural education is the most dependable approach for mitigating hate speech, fostering civility, promoting ethical behavior, and safeguarding responsible freedom of expression. The importance of a broader perspective on the religious attitudes and behavior of Islamic teachers is among the important implications of this research. The researchers recommend that religious moderation literacy be continuously internalized and socialized to Islamic religious teachers.